Molecular Analysis of Oral Bacteria in Heart Valve of Patients With Cardiovascular Disease by Real-Time Polymerase Chain Reaction. Issue 47 (November 2015) - Oliveira, Francisco Artur Forte; Forte, Clarissa Pessoa Fernandes; Silva, Paulo Goberlânio de Barros; Lopes, Camile B.; Montenegro, Raquel Carvalho; Santos, Ândrea Kely Campos Ribeiro dos; Sobrinho, Carlos Roberto Martins Rodrigues; Mota, Mário Rogério Lima; Sousa, Fabrício Bitu; Alves, Ana Paula Negreiros Nunes
Abstract : Abstract: Structural deficiencies and functional abnormalities of heart valves represent an important cause of cardiovascular morbidity and mortality, and a number of diseases, such as aortic stenosis, have been recently associated with infectious agents. This study aimed to analyze oral bacteria in dental plaque, saliva, and cardiac valves of patients with cardiovascular disease. Samples of supragingival plaque, subgingival plaque, saliva, and cardiac valve tissue were collected from 42 patients with heart valve disease. Molecular analysis of Streptococcus mutans, Prevotella intermedia, Porphyromonas gingivalis, and Treponema denticola was performed through real-time PCR. The micro-organism most frequently detected in heart valve samples was the S. mutans (89.3%), followed by P. intermedia (19.1%), P. gingivalis (4.2%), and T. denticola (2.1%). The mean decayed, missing, filled teeth (DMFT) was 26.4 ± 6.9 (mean ± SD), and according to the highest score of periodontal disease observed for each patient, periodontal pockets > 4 mm and dental calculus were detected in 43.4% and 34.7% of patients, respectively. In conclusion, oral bacteria, especially S. mutans, were found in the cardiac valve samples of patients with a high rate of caries and gingivitis/periodontitis.